The herald of freedom - Mandela, Nelson (New Delhi : Mahaveer Publishers, 2012)
Nelson Mandela, b. 1918, freedom fighter and former president of South Africa.
Keywords: Ex-presidents -- Biography. -- South Africa; Politics and government -- 20th century. -- South Africa